Influence of genotype and environment on quality attributes of sweet potato (Ipomea batatas Lam.) (2018)
Sweetpotato is the fifteenth most important food crop, and third between roots and tubers crops worldwide. Sweet potato crop has the capacity to adapt to different environmental conditions, and expression of quality traits is highly influenced by variety and growth conditions. We evaluate the effect of these factors on quality attributes such as dry matter content (DMC), ash content (AC), crude fiber (CF), total protein content (TPC) and brix grades (°Brix) in order to determine adequate conditions to ensure better quality in sweet potato roots.